Analisis Pengungkapan GRI 300 Dalam Laporan Keberlanjutan Perusahaan Industri di BEI Tahun 2023 - Irfani Kemala Fitri; Maya Anggraini; Intan Septi Aulia (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study critically evaluates the quality of environmental disclosure based on GRI 300 standards among industrial sector companies listed on the Indonesia Stock Exchange in 2023. Amidst rising greenwashing concerns in capital markets, this research employs content analysis with a dichotomous scoring approach to sustainability reports. The findings reveal a significant disclosure disparity: while emission (GRI 305) and waste (GRI 306) indicators dominate, biodiversity (GRI 304) and supplier environmental assessment (GRI 308) remain largely neglected. The novelty of this research lies in its uncovering of post-pandemic selective reporting patterns within the industrial sector, demonstrating that corporate transparency remains compliance-driven rather than reflecting substantive accountability. This study contributes to the literature by expanding the application of Legitimacy Theory, suggesting that environmental disclosure serves as a strategic tool to mitigate regulatory pressure. Practically, these findings urge the Financial Services Authority (OJK) to enhance sustainability report auditing standards to mitigate information asymmetry risks for investors.